Verbal Abuse ​against Newly Hired Nurses: ​Prevalence, ​S​ources, ​Reporting, and ​Effect - Fatmeh Alzoubi; Diana Jaradat; Aziza Abujoda (Jordan University of Science and Technology, 2022)
Background: Verbal abuse among healthcare professionals is a common and widespread phenomenon. Objectives: 1) investigate the prevalence of verbal abuse; 2) identify sources of abuse and reasons behind not reporting verbal abuse; 3) examine the effects of verbal abuse on nurses; 4) examine the relationship between socio-demographic characteristics of the newly hired RN’s and exposure to verbal abuse and its personal and professional effects. Methods: A correlational descriptive design was conducted using a sample of 200 participants. Results: High prevalence of verbal abuse is detected among newly hired RN’s in Jordan. The mean score of exposure to verbal abuse was M= 6.76, and the personal and professional effect of verbal abuse scale was M=28.35. The most common sources of verbal abuse were the patient’s family and visitors and other staff nurses respectively (n=147, 74%; n=97, 48.5 %,). It was found that 142 nurses were exposed to verbal abuse but had decided not to report the episode. Exposure to verbal abuse was high in nurses who were divorced and work on a shift system. Conclusion: Being subjected to verbal abuse has a significant effect on nurses’ well-being.   Implications to nursing : Nursing administrators should create programs for training, supporting, and reporting verbal abuse for the newly hired RN’s in Jordan